Diskursus Kalender Hijriyah Global Pasca Kongres Istanbul Turki 2016 - Nihayatur Rohmah (Justicia Islamica, 2017)
In May 2016, Muslims from several countries held the International Hijri Calendar Unity Congress in Istanbul Turkey. At the end of the congress, the result of the voting concluded and published the single calendar system (singular calendar) based on the visibility of the new moon. Calendar is an expression of the collective activity of the rhythm and reflects the resilience and the strength of a civilization. So the existence of the calendar is accurate and consistent as an civilization imperative and is a prerequisite for a civilization to exist and thrive. The characteristic of the revival civilization is when the civilization was able to answer the challenges of the past. Civilization is a mechanism in the social organization, so there is no problem that can not be settled or compromised unless the issue by political or economic interests. There is no difference with the other calendar, the Islamic calendar is a reality that issued by a handful of elite (read: the ruling group of important people in the community). A public position in the affinity people are consumers of course-and practice-calendar produced by their elite. The feature of Hijrah calendar in a country is a clear reflection of the particulars of their elites. Hijrah calendar unity is nothing but a fruit of the unity of authority, and the authority here is Ulil Amri.